Ni2+ doping induced structural phase transition and photoluminescence enhancement of CsPbBr3 - Tao Chen (AIP Publishing LLC, 2021)
All-inorganic CsPbBr3 perovskites exhibit great potential in optoelectronic application due to their outstanding physical properties for optoelectronics. However, the relatively low luminescence efficiency of the bulk CsPbBr3 crystal hampers its further application. Here, we report a facile method to enhance the optical efficiency of halide perovskite powder via doping the transition metal Ni ions. It is demonstrated that Ni doping results in the formation of the Cs(NiPb)Br3 alloy and also triggers the phase transition of CsPbBr3 from orthorhombic to cubic. Both the Cs(NiPb)Br3 alloy and cubic CsPbBr3 are found to contribute to the asymmetric photoluminescence (PL) spectra in the green-yellow light band. The splitting-peak fitting experiments for the overlapped PL spectrum based on the bi-Gaussian line model reveal that the Cs(NiPb)Br3 alloy dominates the contribution of the observed PL enhancement. The Ni2+ doping is also beneficial for optimizing the crystallinity of the CsPbBr3 perovskite, suppressing the nonradiative recombination and significantly enhancing the photoluminescence consequently. Our investigation provides a novel insight into the effect of environmentally friendly metal doping in perovskites.